Analysis on filtering performance of solar powered water treatment device (SWAD) prototype - Ismail I.N.B.; Khean F.F.; Zawawi M.H.; Zahari N.M.; Abidin S.Z.; Yusairah W.N.; Zuhdi A.W.M.; Kamarudin K.; Zawawi M.F.B.M.; Basir M.H. (American Institute of Physics Inc., 2023)
Treated water is an improved water quality and very essential for aquaculture or for domestic usage at remote area. One of the process to treat water is by filtration. A solar powered water treatment device (SWAD) prototype was built to cater this demand. SWAD is basically a floating water filter which operates in a self-sustainable way on calm water body such as lake or pond. Solar panel is used to generates electricity to power the pumps to suck water into the filter. This paper discusses the filtering performance of the prototype by taking UNITEN Lake as the venue for the test. The tests show significant results on the activated carbon filter where the contaminants are removed effectively. The activated carbon is able to filter water in an effective and efficient way. 2019 Author(s).